SOCIAL REABILITATION MODEL FOR TEENAGERS WITH DEVIANT BEHAVIOR IN CLOSED-TYPE INSTITUTIONS - Y. V. Moskvina (Образование и наука)
The paper considers educational practices in the closed-type institutions for teenagers with deviations in legal, intellectual and psychoemotional behavior, and reveals a social rehabilitation model for this category of teenagers. The model is based on A. V. Petrovsky’s concept of the three phases of personality development in adolescence – adaptation, individualization and integration. The author presumes that any deviation in a teenager’s behavior increases as the result of negative experience, developed and retained in asocial surroundings. The goal of teaching staff in closed-type institutions is to transform the trend of deviant behavior into the normal attitude of social adaptation. The author emphasizes a need for positive experience of passing the above phases in friendly atmosphere with adequate behavior patterns. Preventive work implies the priority changes – i.e. the prevalence of the future over the past, self-determination (revision of goals, meanings, and attitudes to a free choice), reorientation from ≪I don’t want, I can’t, I don’t have to≫ to the positive connotations of ≪I have to, I can, I want≫. The paper denotes the methods and ways of pedagogical facilitation, relating to different phases of educational process, and provides a technique for regular monitoring of personal behavior changes, including the key evaluation positions and scales. The paper is addressed to the teaching staff involved in rehabilitation of teenagers with deviant behavior.